Vision Related Quality of Life of Adult Patients Undergoing Cataract Surgery at A Tertiary Hospital in Dar es Salaam (Tanzania Medical Journal, 2022)
BackgroundCataract is the leading cause of visual impairment in adults, and it is the overall leading cause of blindness worldwide. Health-related quality of life of patients with poor vision due to cataract is reported to be low. Cataract surgery is aimed to restore vision and as a result, is expected to improve visual function and quality of life. The purpose of this study was to determine the visual outcome and changes in the quality of life of patients undergoing cataract surgery at Comprehensive Community-Based Rehabilitation in Tanzania (CCBRT) hospital.MethodA quantitative prospective longitudinal hospital-based study which recruited 153 adult participants scheduled for cataract surgery at CCBRT hospital was conducted. All patients were interviewed before and two months after surgery using the Visual Function Questionnaire-25(VFQ-25). Pre and post-operative standard visual acuity assessment was done. We analyzed data by the use of SPSS version 23.ResultsOne hundred forty-three participants were analyzed. The mean age (SD) was 66.47 ±10.25 years. There was a significant increase in the visual acuity post cataract surgery (p=0.001) with a good outcome of 82% as per WHO criteria. The Quality-of-life assessment was low before surgery, it however significantly improved after surgery (p <0.002) with a 19.3 points increment in overall composite scores. All subscale scores had improved and were statistically significant. Most patients, who had difficulty doing different activities due to poor vision, were able to resume their activities two months after surgery.ConclusionPoor vision due to cataract leads to reduced vision-related quality of life. Consequently, patients fail to participate in daily social and economic activities. We have noted a significant improvement in the visual acuity and vision-related quality of life post cataract surgery.RecommendationsAs the population ages, there is an increase in backloading of cataract and hence there is a need to increase cataract surgical uptake and parallelly make the services easily available over the whole country. Since the good outcome of cataract surgery was associated with good quality of life, monitoring of surgical outcomes of cataract should be made regularly and routinely. This will help to identify and address any shortcomings related to visual outcome to improve the quality of cataract surgery and hence the quality of life of patients undergoing cataract surgery.